Full-Time Integral Education: conceptions present in teaching practice in a municipal Elementary School (Práxis Educativa, 2020)
The objective of this work is to apprehend the conceptions regarding Full-Time Integral Education in the context of teaching practice in an Elementary School in the city of Ponta Grossa-Paraná-Brazil. The methodological referral corresponds to the case study with the qualitative analysis of the data. Eighteen teachers from the 1st and 2nd Cycles of Elementary School (1st to 5th grade) were research subjects. Data were collected in the period between May and June 2018 through a questionnaire via Google Forms. The empirical data revealed the insufficiency, lack and, at times, the non-existence of specific initial and continuing training in Full-Time Integral Education with a focus on the expansion of time and the educational spaces added to a concept of Integral Education.Keywords: Full-Time Integral Education. Teaching practice. Elementary School. Public school.